Kinetic studies of the CIO plus CIO association reaction as a function of temperature and pressure - Boakes, G; Mok, WHH; Rowley, DM (ROYAL SOC CHEMISTRY, 2005)
The kinetics of the association reaction of ClO radicals: ClO + ClO + M -> Cl2O2 + M (1), have been investigated as a function of temperature T between 206.0-298.0 K and pressure p between 25-760 Torr using flash photolysis with time-resolved UV absorption spectroscopy. ClO radicals were generated following the photolysis of Br-2/Cl2O mixtures in nitrogen diluent gas. Charge coupled device (CCD) detection of time resolved absorptions was used to monitor ClO radicals over a broad wavelength window covering the ClO (A (II)-I-2 <- X (II)-I-2) vibronic absorption bands. The high pass filtered ClO absorption cross sections were calibrated as a function of temperature between T = 206.0-320 K, and exhibit a negative temperature dependence. The ClO association kinetics were found to be more rapid than those reported in previous studies, with limiting low and high pressure rate coefficients, in nitrogen bath gas, k(0) = (2.78 +/- 0.82) x 10(-32) x (T/300)(-399 +/- 0.94) molecule(-2) cm(6) s(-1) and k(infinity) = (3.37 +/- 1.67) x 10(-12) x (T/300)(-149 +/- 1.81) molecule(-1) cm(3) s(-1), respectively, (obtained with the broadening factor F-c fixed at 0.6). Errors are 2 sigma. The pressure dependent ClO association rate coefficients (falloff curves) exhibited some discrepancies at low pressures, with higher than expected rate coefficients on the basis of extrapolation from high pressures (p > 100 Tort). Reanalysis of data excluding kinetic data recorded below p = 100 Torr gave k(0) = (2.79 +/- 0.85) x 10(-32) x (T/300)(-3.78 +/- 0.98) molecule-(2) cm(6) s(-1) and k infinity = (3.44 +/- 1.83) x 10(-12) x (T/300)(-1.73 +/- 1.91) molecule(-1) cm(3) s(-1). Potential sources of the low pressure discrepancies are discussed. The expression for k(0) in air bath gas is ko = (2.62 +/- 0.80) x 10(-32) x (T/300)(-3.78 +/- 0.98) molecule(-2) cm(6) s(-1). These results support upward revision of the ClO association rate coefficient recommended for use in stratospheric models, and the stratospheric implications of the results reported here are briefly discussed.